Adoção da computação em nuvem, relação custo-benefício e estratégias para seleção de provedores: uma revisão sistemática - PAULA, Antonio Carlos Marcelino de (2016)
Context: Cloud computing has been one of the most promising computing paradigms in industry, been well-known for its proposed advantages when compared to traditional computing models. With cloud resources, organizations have the possibility to fund applied resources on a demand basis. This scenario allows the most effective allocation of investment in IT resources, a fact that has been a market attractive in the current scenario of the global economy. However, to make use and benefit fully from these advantages, organizations need to plan the migration of their applications to the cloud. Goal: Identify relevant studies published in the literature that address experience reports on migration opportunities and adoption of cloud computing, the cost-benefits relationship of this adoption and selection strategies of service providers that are suitable for the needs of the organization profile. Method: Perform a systematic review of the literature and then a characterization of case studies also collected from the literature to compare strategies reported by organizations to migrate and adopt cloud computing. Results: The results of these studies show that a representative sample of the organizations carries out the adoption process of an innovation influenced by technological, organizational and environmental issues. The cost, performance and security/privacy appear as relevant factors by enterprises when deciding for the adoption. Note also a trend in the use of public deployment model and model Infrastructure as a Service (IAAS). Conclusion: Due to the variety of strategies, approaches and related tools in selected studies, hopefully that the results of this study support the companies in deciding the most appropriate strategy for cloud adoption, in the cost-benefit relationship of this adoption, and the selection of service providers that best meet your expectations. These findings may be a useful reference for developing guidelines for adoption and effective use of cloud computing.